When student midwives are present during labour and childbirth in a peer-learning model: An interview study of parents in Sweden. (January 2022) - Zwedberg, Sofia; Barimani, Mia
Highlights: Parents were willing to contribute to student midwives' education. Parents supported the peer-learning model during labour and childbirth. Parents took advantage of the learning situation. Abstract: Objective: For peer learning to be useful in clinical practice, we need to know how parents experience peer learning during labour and childbirth. This study explored how parents experienced having two students present during labour and childbirth in a peer-learning model. Design: A qualitative approach using individual interviews followed by thematic inductive analysis. Setting: Three hospitals and obstetric units in Stockholm, Sweden. Participants: Eleven women and nine partners. Findings: The overarching theme was that of a fruitful model of health care, in which there were gains for both parents and students. Parents described feeling seen and cared for, being made aware of what was going on, and never being left alone ( subtheme 1, Trustful relationship). Parents appreciated being able to observe student midwives' attendance to the tasks at hand and that they, the two students, learned from each other (subtheme 2, Advantages for students). Conclusions: The parent couple was able to build a trustful relationship with both students. Furthermore, could parents only see advantages for students in a peer-learning model. Parents reported generous support and were willing to contribute to student education. Parents took advantage of the learning taking place between the two students. The model deserves to be incorporated in the midwifery-student internships to complement more individually assisted births.